Securing Pension Provision - Blair, C. author. aut Link
X, 152 p.
Keywords: By comparing Germany, France, the UK and the USA this study explores how governments have tackled the increased pressure of financing state pensions. Specifically, it looks at the approach of each of these countries to raising the age of entitlement in order to understand the ways in which this policy was introduced in different countries.